The Challenges and Future of the Malay Language and Literature in Navigating the Era of Artificial Intelligence (AI) - Zainudin, Zaheril (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
Artificial Intelligence (AI) technology has triggered significant transformations across various domains of life, including the field of the Malay language and literature. This concept paper critically analyses the challenges and future prospects of the Malay Language and Literature within the context of AI dominance. The discussion focuses on issues such as the dominance of foreign languages in AI systems, the limited availability of Malay-language corpora in machine learning models, and the technological infrastructure constraints that hinder the advancement of Malay natural language processing (NLP). Furthermore, the paper explores sociocultural implications arising from the marginalisation of the mother tongue in digital interactions. Through a qualitative approach supported by contemporary document content analysis, this paper identifies the urgent need to develop large-scale Malay linguistic corpora, establish a national digital language policy, and strengthen strategic collaborations between the education sector, industry, and government. The discussion also proposes strategic initiatives to empower the Malay language in technology, including the development of localised language models, the integration of language elements into AI education curricula, and the production of high-quality digital literary content. Findings indicate that the sustainability of the Malay language in the AI era depends on the collective commitment of all stakeholders to integrate it as a vital component of a modern and competitive digital ecosystem. The implications of this study are significant for policymakers, academics, as well as technology and cultural practitioners who aspire to ensure the continued relevance and functionality of the Malay language in a global landscape increasingly driven by artificial intelligence.
Keywords: Malay; literature; artificial intelligence technology; NLP; digital policy.